MENGGALI REALITAS KEPATUHAN WAJIB PAJAK PEMILIK USAHA MIKRO KECIL DAN MENENGAH (UMKM) RESTORAN KAMPOENG POPSA DITENGAH PANDEMI COVID-19 - Tenriwaru, Tenriwaru; Syahra Wirdiya, Andi Khatmi; Samad, St. Sukmawati (Economos : Jurnal Ekonomi dan Bisnis, 2020)
The aims of this research to find out the compliance of taxpayers of small and medium enterprises (UMKM) in Kampoeng Popsa Restaurant during the Covid-19 pandemic, due to the economic slowdown caused by the suggestion of working from home. This has an impact on the income of micro small and medium enterprises (UMKM). The method used is a qualitative method with a phenomenological approach that describes the experience or phenomenon experienced by a phenomenological approach. The location of this research was conducted in the city of Makassar in this study is as many as 3 UMKM taxpayers and 1 employee of The Directorate General of Taxes. The data is collected through direct interviews with each informant, observation, and documentation. The data has been collected later in the analysis using the phenomenological approach. The results of this study showed that the informants do not understand taxes, so informants can define taxes based on their perceptions. While the reality arising from paying taxes tends to lead to negative if the tax payment is not properly accounted for by the relevant party.